2017
DOI: 10.1007/s10681-017-1910-8
|View full text |Cite
|
Sign up to set email alerts
|

QTL detection for flowering time in faba bean and the responses to ambient temperature and photoperiod

Abstract: Springer is a green publisher, as we allow self-archiving, but most importantly we are fully transparent about your rights. Publishing in a subscription-based journal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Importantly, lines have been detected with greater variation in photoperiod and temperature response than observed in the QTL study run alongside this one (Catt et al 2017). Together with further studies to understand better the mechanisms behind the environmental responses (particularly vernalisation, and optimum temperatures), the loci (and corresponding markers and candidate genes) implicit in conferring the variation in temperature and photoperiod response seen in this study could be identified using lines that represent the greater variation as parents in future QTL mapping populations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Importantly, lines have been detected with greater variation in photoperiod and temperature response than observed in the QTL study run alongside this one (Catt et al 2017). Together with further studies to understand better the mechanisms behind the environmental responses (particularly vernalisation, and optimum temperatures), the loci (and corresponding markers and candidate genes) implicit in conferring the variation in temperature and photoperiod response seen in this study could be identified using lines that represent the greater variation as parents in future QTL mapping populations.…”
Section: Discussionmentioning
confidence: 91%
“…Further to this, supra-optimal temperatures have been observed to delay flowering for some species and in a study in wheat (Triticum aestivum L.) by Appendino and Slafer (2003), allelic variation at one gene determined whether a plant would have the same TTF in both 16°C and 23°C, or would flower in 342 degree-days less under 16°C than 23°C. A study run simultaneously to this one (Catt et al 2017) focussed on detecting quantitative trait loci (QTL) for flowering time and responses to photoperiod and ambient temperature. The study detected eight regions of flowering QTL in an Icarus × Ascot recombinant inbred line population with four of the regions found to be associated with photoperiod response and two of the regions associated with temperature response.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in chickpea or lentil, major QTLs corresponding to flowering time have been reported 26 31 , but only in a few cases 32 , the orthology with other crops or model species has been assessed. In case of faba bean, just a few QTL analyses for flowering time have been reported 33 36 but no information on the underlying genes and possible orthology, is currently available.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in fava bean (Vicia faba) under SD-HT many small QTLs were revealed compared to LD conditions (Catt et al 2017 Bolting-owering QTLs on chromosome 2 have been mapped in other RIL populations from inter and intra speci c crosses and qBFr2.1 consistently had a signi cant additive effect in high temperature (HT) conditions (Hartman et al 2012;Jenni et al 2013). Furthermore, an L. serriola accession used in previous bolting studies (Hartman et al 2012) had the same P allele for marker LZ001, linked to the qBFr2.1, as PI 251246.…”
Section: Discussionmentioning
confidence: 99%